Transition to Independent Surgical Practice and Burnout Among Early Career General Surgeons. (April 2022) - Firdouse, Mohammed; Chrystoja, Caitlin; de Montbrun, Sandra; Escallon, Jaime; Cil, Tulin
Background : The transition from surgical residency to independent practice is a challenging period that has not been well studied. Methods : An email invitation to complete a 55-item survey and the Maslach Burnout Inventory–Human Services Survey (MBI-HSS) was sent to early career general surgeons across Canada. The chi-square test or Fisher's exact test was used to compare demographic and survey characteristics with burnout. Multivariable logistic regression was performed. Results : Of the 586 surgeons contacted, 88 responded (15%); 51/88 surgeons (58.0%) were classified as burnt out according to the MBI-HSS. Most surgeons (68.2%) were not confident in their abilities to handle the business aspect of practice. The majority (60.2%) believed that a transition to independent practice program would be beneficial to recent surgical graduates. Conclusions : Our data showed high prevalence of burnout among recently graduated general surgeons across Canada. Further, respondents were not confident in their managerial and administrative skills required to run a successful independent practice.